An Assessment of TESDA Scholarship Programs - Aniceto Jr. C. Orbeta; Michael Ralph M. Abrigo (Philippine Institute for Development Studies (PIDS), 2012)
This paper reports on the results of the review of the two major scholarship programs of TESDA, namely: (a) the Training for Work Scholarship Program (TWSP); and (b) the Private Education Student Financial Assistance (PESFA). The two scholarship programs account for 73 percent of the number of scholars among the TVET graduates in 2007 (TESDA 2010a). The paper was commissioned by the Department of Budget and Management (DBM) to be an input to the current effort of the Philippine government to improve the policy-basis and result orientation of the budgeting process.The primary objectives of the study are to determine (a) the internal efficiency (through the drop-out rate); and (b) the external efficiency (through the rate of employment) of scholars of the TESDA technical-vocational scholarship programs. Given the limited time and resources, the study had to rely on data generated by TESDA. In particular, it did a re-analysis of the 2008 Impact Evaluation Study (IES) survey data to generate empirical evidence on the various issues of the study. It also used data from reports regularly submitted by the technical-vocational institutions (TVIs) to TESDA for one region - the National Capital Region (NCR). This data set is the primary source of official TVET statistics. Administrative data from the implementing units of the scholarship programs were also used. In addition to these data sets, three separate focused group discussions (FGDs) involving relevant decisionmakers were also done. One was with national TESDA officials, another with the regional TESDA officials, and third was with the officials of the TVIs and TVI employers.The assessment shows that the scholarship programs are performing well in terms of internal efficiency as indicated by the high graduation rates particularly in recent years. They are not performing well though in terms of external efficiency as indicated by low employment rate. It is important to emphasize, however, that compared to general TVET graduates, the scholars, particularly PESFA scholars, but not TWSP scholars, are performing slightly better compared to nonscholars in terms of employment. It appears that the low external efficiency performance is a general TVET sector problem and not a problem specific to the scholarship programs.
Keywords: I22; J24; 330; Philippines; vocational and technical education and training; TVET scholarships